2015
DOI: 10.3892/mmr.2015.3373
|View full text |Cite
|
Sign up to set email alerts
|

Expression of integrin-binding protein Nischarin in metastatic breast cancer

Abstract: The present study aimed to investigate the expression of Nischarin protein in primary breast cancer (PBC), and to evaluate its role in tumor metastasis. Paired specimens of breast cancer tissues and adjacent normal tissues were surgically obtained from 60 patients with PBC at the Zhejiang Cancer Hospital (Hangzhou, China). Nischarin protein concentrations were determined by an ELISA assay. Breast cancer tissues exhibited a significantly lower concentration of Nischarin (5.86±3.19 ng/ml) compared with that of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Within the past two decades, the novel protein Nischarin has been revealed to serve as a tumor suppressor in ovarian and breast cancers (1)(2)(3)(4). Nischarin expression levels are different in breast cancer cell lines with different degrees of malignancy (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the past two decades, the novel protein Nischarin has been revealed to serve as a tumor suppressor in ovarian and breast cancers (1)(2)(3)(4). Nischarin expression levels are different in breast cancer cell lines with different degrees of malignancy (4).…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the mRNA level of Nischarin is associated with an increase in cell invasiveness (2,4). In human breast tissues, the expression level of Nischarin in cancerous tissues is significantly lower compared with that in non-cancerous tissues (2)(3)(4), lower in cancer tissues with lymph node metastasis compared with those without (3), lower in increasing grades 1-3 of invasive cancer tissues (2), and lower in advanced stage breast cancer tissues compared with those in the early stage (4).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of human breast cancer patient tumors revealed that tissues with lymph node metastasis have significantly decreased levels of Nischarin than patients without lymph node metastasis (37). In addition, LOH studies performed using microsatellite markers in DNA samples from 18 human breast cancers and their normal tissue counterparts, revealed that LOH is seen in 50% of human breast cancer patients, which results in decreased Nischarin expression (12).…”
Section: Nischarin Is a Tumor Suppressor Of Breast Cancermentioning
confidence: 99%